Asphalt Collectors â€“ a Solution for the Humid and Hot Climates - Khoja, Ahmed; Waheeb, Sahl (International Journal of Engineering and Technology, 2018)
The Asphalt Solar Collectors (ASC) technology is well known for his its application in moderate to cold climate; however there is a need to explore a wider scope for this application. This research is an attempt to explore the Asphalt collectors as a solution for the hot and humid climate. The paper explored this by analyzing the performance of the 20mÂ² ASC meeting the demand of the domestic hot water, solar assisted cooling and the atmospheric water generation.Â